2008
DOI: 10.1242/dev.015859
|View full text |Cite
|
Sign up to set email alerts
|

Signals from the neural crest regulate beta-cell mass in the pancreas

Abstract: *Pancreatic islet cells and neurons share common functions and similar ontogenies, but originate in different germ layers. To determine whether ectoderm-derived cells contribute instructive signals to the developing endoderm-derived pancreas, we defined the chronology of migration and differentiation of neural crest cells in the pancreas, and tested their role in the development of the islets. The homeodomain transcription factor Phox2b marks the neural precursors from the neural crest that colonize the gut to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 45 publications
6
83
1
1
Order By: Relevance
“…1b). NCSCs indeed have a strong capacity to migrate in vivo and in vitro [8,10] and thus are able to migrate into the islets, making cell-cell contacts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1b). NCSCs indeed have a strong capacity to migrate in vivo and in vitro [8,10] and thus are able to migrate into the islets, making cell-cell contacts.…”
Section: Resultsmentioning
confidence: 99%
“…The endocrine pancreas is normally richly innervated with sympathetic, parasympathetic, sensory, peptidergic and nitric oxide synthase containing neurons that help to modulate hormone secretion [1][2][3]. In rodent models, signals from the neural crest are important in regulating beta cell mass during development [7,8] and neural signals are involved in the adaptive increase of beta cell mass in obesity [37]. There are several studies suggesting that neurotrophins, such as nerve growth factor and brain-derived neurotrophic factor, may affect the growth of both nerves and beta cells in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been proposed that nonmesodermal-derived stem cells support beta-cell replication. Different studies found that beta-cell growth may be affected by neurotrophins [51,52], and that neural crest stem cells (NCSC) have an important role in beta-cell differentiation by regulating beta-cell mass during development [53]. On the basis of these observations, Olerud et al investigated whether co-transplantation of islets and neurospheres derived from NCSC is beneficial for survival, growth, and function of transplanted beta-cells [54].…”
Section: Mechanism Of Diabetes Reversal Through Co-transplantation Ofmentioning
confidence: 99%
“…In both type 1 and type 2 diabetes, dysregulation of glucose homeostasis and b-cell function and loss of b-cells are responsible of hyperglycemia (1). b-cells are neuroendocrine cells arising from precursor cells of the embryologic neural crest (2,3). Pancreatic b-cells regulate a large variety of body functions through paracrine and endocrine actions via dedicated amines and peptides, including the neurotransmitter serotonin.…”
mentioning
confidence: 99%